Developing a methodology for reducing diamond breakage within processing plant - Chele, Motsi John (Department of Chemical Engineering, 2021)
Diamond breakage has been a problem experienced by diamond operations. Material breakage characterisation methods has been used to determine the hardness or resistance to breakage of diamond host rock, ceramic diamond simulants and simulants embedded in the concrete blocks. This establishes a relationship between specific input energy and degree of breakage that can be used for size reduction to minimise diamond breakage. Ceramic diamond simulants have been used in the process to identify areas that are more prevalent to diamond breakage. It was found that sections of high impact such as the cone crushers and drop height in the surge bins had the highest risk of diamond breakage. Kimberlite ore and ceramic diamond simulants were subjected to compressive breakage in drop weight test. The progeny particle size distribution and degree of breakage were compared. Standard breakage characterisation models were fitted to the breakage data of tested material and relative hardness parameters determined to establish the energy threshold. The breakage tests results showed that the ceramic diamond simulants were very hard while the kimberlite ore and concrete blocks were medium to soft. The material hardness parameters were determined from fitting the breakage data to the standard impact breakage characterisation models (t10-Ecs breakage model and Size dependent breakage model). Concrete blocks and Kimberlite ore showed less resistance to compressive breakage as demonstrated by higher A values compared to the ceramic diamond simulants. Applying material hardness categories presented by Napier-Munn et al (1999), Kimberlite ore was soft, concrete blocks ranged medium to soft and ceramic diamond simulants very hard. The remedial measures implemented in the process were to rubber line the concentrate bins in the recovery to minimise the impact forces, as well the surge bins in the process plant were controlled in such a way that reduces the drop height. Finally, the cone crushers and pan feeders operating philosophy has been improved to start at high speed to achieve choke feed conditions faster and to promote interparticle crushing. The close side settings were also optimized to reduce liner to liner interaction rather enhance particle-to-particle interaction. Through the optimised process, it had been observed that the diamond breakage had dropped below 5% level of the total stones recovered at +5cts. The methodology developed proved to be working after being tested in the chosen flowsheet.